STUDY OF THE EFFECT OF FAMILY ENVIRONMENT ON THE EDUCATIONAL ACHIEVEMENT OF SECONDARY LEVEL STUDENTS - Prachi; Singh, Manu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present study is a study of the effect of family environment on the educational achievement of secondary level students. In this study, a comparative study of the educational achievement of students with high, medium and low family environment has been done. In the present study, survey method has been used under descriptive research. The students studying in secondary schools located in the urban area of ​​Mathura district have been considered as the population. The secondary schools have been selected by objective method, after which 100 boys and 100 girls studying in it, i.e. a total of 200 students have been selected by stratified random method. As a tool, the Family Environment Schedule prepared by K.S. Mishra and the marks obtained by the students in the Class 10 examination have been kept as educational achievement. For the analysis of the data, the variance method (ANOVA) and the t-ratio statistical method have been used. In the conclusion of the present study, it was found that the family environment has an effect on the educational achievement of the secondary level students, that is, the educational achievement of the students with high, middle and low family environment is different from each other.